130 Improving Documentation of Bowel Movement on Geriatric Wards. (16th March 2021) - Noar, A; Parkin, J; Hallam, R; Wijekoon, T; Walker, C; Khan, H; Tsui, J; Chin, K; Chakravorty, M; Zalynda, R
Abstract: Introduction: Constipation is a widely prevalent issue in older adults that may result in complications such as urinary retention, delirium and bowel obstruction. Previous studies have indicated that while stool charts are well completed by nursing staff, they are infrequently monitored by doctors. This project aimed to improve the documentation of bowel movement by doctors on ward rounds to 85%, by the end of a 3-month period. Methods: Formulation of the project was achieved using group work and a fishbone diagram which focussed on how doctors can improve on documenting bowel movements. Baseline data were collected from inpatient notes on weekdays over a three-week period on a geriatric ward in Northern General Hospital, Sheffield. Interventions of posters and stickers of the poo emoji were placed on walls and in inpatient notes respectively as a reminder. Post-intervention data were collected on weekdays over two weeks, and then repeated a month later to assess for a sustained change. Results: The data on bowel activity documentation were collected from 28 patients. The baseline data showed that bowel activity was monitored daily on the ward 56.25% of the time. There was a significant increase in documentation of 85.75% following the interventions. The sustainability study showed that bowel activity was documented on the ward 59.09% of the time. Conclusions: This study shows how a strong effect on behavioural change can be accomplished through simple interventions such as stickers and posters. As most wards currently still use paper notes, this is a generalisable model that other wards can trial. However, this study also shows the difficulty in maintaining behavioural change over extended periods of time. Further PDSA cycles should examine the reasons behind the difficulty sustaining the change and implement new changes that aim to overcome them.